PENGUKURAN ROA, ROE, NPM TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN JAMU DAN FARMASI PERIODE 2016-2020 - Faramita Dwitama; Cicilia Erly Istia; Rini Dwiastutiningsih (Jurnal Ekonomi dan Manajemen, 2022)
This research aims to determine the ability of herbal and pharmaceutical companies to earn profits and the effect of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) on the profits earned. The profit growth is used by the industry to see the development of the industry in creating profits. The sample of this research is the financial statements of herbal and pharmaceutical companies for the period 2016-2020. After processing by SPSS software, the test result obtained at herbal and pharmaceutical companies indicates that there is a significant effect of the independent variables simultaneously on the dependent variable, so that Ha is accepted. This means that there is a positive and significant influence on the NPM, ROA, and ROE variables on Company’s Profits. So that the higher the values of NPM, ROA and ROE are produced, the higher the company’s profits earn.